Diet and mental health in school-aged children: a mini review of school-based dietary intervention studies - Coxon, Christle; Gibson, E. Leigh (Frontiers in Education, 2025)
School-based dietary interventions are implemented to improve health outcomes in children and adolescents, yet their impact on mental health and wellbeing remains underexplored. This mini-review synthesized findings from seventeen interventions assessing behavioral functioning and mental health symptoms in children (6–12 years) or adolescents (13–18 years). Most studies were conducted across multiple sites, enabling recruitment of large, diverse populations. More studies were conducted in children compared to adolescents. Behavioral outcomes such as hyperactivity, inattention, and oppositional behavior were commonly assessed in younger children via parent or teacher reports, while adolescent studies more frequently measured mental health symptoms, including depression and anxiety, through self-report. Supplementation, particularly in the context of nutrient deficiencies, was associated with modest improvements in behavioral functioning in children and mental health symptoms in adolescents. However, outcomes varied by the assessor (parent or teacher), and some studies showed placebo effects. In contrast, food reformulation interventions showed no significant impact on mental health outcomes. Despite the use of validated tools, methodological limitations, and variation in participants’ nutritional status limit interpretation. Overall, school-based dietary interventions show potential to improve mental health by reaching large, diverse populations. Further research is needed using standardized, age-appropriate measures and incorporating assessment of nutritional status to understand how diet can support and improve mental health in children and adolescents.